Enumerating Predation on Chinook Salmon, Delta Smelt, and Other San Francisco Estuary Fishes Using Genetics. (23rd June 2021) - Brandl, Scott; Schreier, Brian; Conrad, J. Louise; May, Bernie; Baerwald, Melinda
Abstract: The establishment of nonnative predatory fish species is a worldwide phenomenon often having adverse effects on native species. Trophic interactions are complex, and uncertainty is a common theme in discussions of nonnative predator management. Several fishes of the San Francisco Estuary have experienced significant declines in recent decades due to multiple factors, including habitat alteration and predation. The role of predation as a direct cause of mortality remains an open question, as does whether habitat conditions play a role in promoting predation on species of concern. Recent studies using visual identification of prey have found little to no evidence of predation on species listed under the Endangered Species Act such as Delta Smelt Hypomesus transpacificus and juvenile Chinook Salmon Oncorhynchus tshawytscha . To increase the likelihood of detecting predation, this study employed a genetic approach. We combined this technique with habitat and water quality data to investigate the role that habitat may be playing on incidence of predation. This study focused on detection of predation on Chinook Salmon and Delta Smelt, six other native fish species, and six nonnative fish species by Striped Bass Morone saxatilis and other piscivores. Unlike previous studies in the region, the proportion of predators with no prey detected in their gut contents was high (47–81%). The study detected Delta Smelt in 1.3% of Striped Bass—considerably higher than other contemporary predation studies in the Sacramento–San Joaquin Delta. In April 2014, 6.6% of Striped Bass were positive for Chinook Salmon—substantially higher than observed in recent visual diet studies. Interestingly, native species comprised a relatively high proportion of Striped Bass prey (60%). Water temperature and conductivity were identified as significant predictors of Chinook Salmon presence in Striped Bass gut contents. This research also suggests that predation on soft‐bodied prey may be an overlooked segment of the diets of piscivores.